Competency-Based Syllabus and Skills-Based Syllabus of Arabic Learning in College - Nuraini, Nuraini (Universitas Islam Negeri Raden Intan Lampung, 2019)
A challenging and uncertain millennial era requires that educational institutions design their education based on real needs in the field capable of producing human resources with attitude, knowledge and skill competencies, in order to prepare this, syllabus plays an important role because it is one of the stages of the curriculum, to answer what to learn to deal with this problem. Competence can be interpreted as knowledge, skills, and abilities controlled by someone who has become part of himself. So that he can perform cognitive, affective and psychomotor behaviors as well as possible.This study uses a development research method developed by Jack Richard which modified according to the needs in the development of the syllabus. Thus, the research steps include the study of documents on the syllabus that is already running, observation of learning using a running syllabus, and analysis of needs for the development of the syllabus, and developing the syllabus for Arabic language learning in higher education. The skill-based syllabus contains a number of specific